2023
DOI: 10.3390/ijms24054254
|View full text |Cite
|
Sign up to set email alerts
|

The Main Theories on the Pathogenesis of Endometriosis

Abstract: Endometriosis is a complex disease, which is defined by abnormal growth of endometrial tissue outside the uterus. It affects about 10% of women of reproductive age all over the world. Endometriosis causes symptoms that notably worsen patient’s well-being—such as severe pelvic pain, dysfunction of the organs of pelvic cavity, infertility and secondary mental issues. The diagnosis of endometriosis is quite often delayed because of nonspecific manifestations. Since the disease was defined, several different patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 51 publications
0
45
0
10
Order By: Relevance
“…Some studies showed that endometriosis patients have elevated neutrophils in their blood and peritoneal uid [47,48]. This may happen because endometriotic tissue makes factors that attract and activate neutrophils [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that endometriosis patients have elevated neutrophils in their blood and peritoneal uid [47,48]. This may happen because endometriotic tissue makes factors that attract and activate neutrophils [49].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes are alterations of gene expression without changes in DNA sequence. The epigenetic regulation of CSCs occurs via (1) DNA methylation, (2) alterations to the chromatin architecture that are either due to the post-translational modification of histones or the activity of polycomb group proteins, as well as (3) a modified spectrum of microRNAs [ 11 , 105 ].…”
Section: Epigenetic Events In Pancreatic Cancer Stem Cellsmentioning
confidence: 99%
“…18 Endometriosis occurs when cells of the endometrium travel outside of the uterus and implant on surfaces of other organs or structures of the pelvic cavity, such as the ovaries, fallopian tubes, uterus, bowel, and bladder, or even outside of the pelvic cavity, such as on or in the abdominal wall. 19 Th e inserted cells proliferate and grow into a web of tissue causing adhesions that connect the organs and tissue of the pelvis, resulting in the pulling, pressure, and tearing sensations experienced by patients. Laparoscopy is the gold standard for diagnosis of endometriosis.…”
Section: Th Ree Common Causes Of Dyspareunia Are Vulvodynia Postpartu...mentioning
confidence: 99%